A Discourse Analysis on “Under the Same Sun” from Scorpions - Win Listyaningrum Arifin (Journal of Pragmatics Research, 2019)
The song "Under the Same Sun" firstly released in 1993 is a song written by famous rock group music namely Scorpions. This group is coming from Hannover, Germany. Though renowned phenomenally as a music group with loud genre but this song is a ballad one because it really tells the story of real-life people in the war zone while citizens of the world just show a little caring concern. The song portraits a common view on the hopelessness of victimized people in war zone who need for sympathy and empathy. Otherwise, they get no positive response from other people who live in comfort. This paper is a library research with a descriptive qualitative approach to investigate the discourse analysis of a song lyric. The approach is then used to analyze the data from the song lyrics. The discourse aims at finding the discourse on its grammatical aspect, lexical aspects, situational aspect, and contextual aspect. The study’s discourse analysis on the song lyrics reveals several features. From the grammatical aspect of this song revealed the references in the form of pronoun and demonstrative, ellipsis and conjunction. While in the lexical aspects, it found only two components, namely reps and collocation. The contextual analysis showed the cultural context and the context of the situation. Meanwhile, the situational context itself is divided into physical context, epistemic context and social context.Keywords: Grammatical Aspect, Lexical Aspect, Contextual Aspect